Estrogen Receptor Beta Induces JNK Pathway Regulation and the Effect of High-Dose Boron on Rat Splenic Lymphocytes - Zhang, Kaihuan; Wang, Chen-Fang; Zhang, Feng; Li, Jian; Tang, Zhongtao; Jin, Erhui; Gu, Youfang (Current topics in nutraceuticals research, 2024)
The regulatory role of estrogen receptor beta (ERβ) and the JNK signaling pathway in the effect of high-dose boron on rat splenic lymphocytes has been examined by measuring proliferation, apoptosis, and immune function. The results showed that, compared with the control group, the addition of high-dose boron (40 mmol/L) reduced the proportion of CD3+, CD4+, and CD8+ T lymphocytes, the concentrations of IgG, IL-2, IFN-γ, and IL-4, the proliferation rate of splenic lymphocytes, and the expression levels of PCNA and Bcl-2 mRNA (P < 0.01 or P < 0.05), and increased the apoptosis rate of splenic lymphocytes, caspase-3, and BAX mRNA expression levels (P < 0.01 or P < 0.05). After specific blocking of ERβ, the addition of high-dose boron could not reduce the proportion of CD8+ T lymphocytes, the concentrations of IgG and cytokines IL-2, IFN-γ, and IL-4, the lymphocyte proliferation rate, or PCNA mRNA expression levels, nor could it increase BAX mRNA expression levels. After specific blocking of JNK, the addition of high-dose boron could not increase BAX mRNA expression levels. However, after specific blocking of ERβ and JNK, the addition of high-dose boron could neither reduce the proportion of CD4+ and CD8+ T lymphocytes, the concentrations of IgG and IL-2 (P = 0.05), nor increase caspase-3 and BAX mRNA expression levels (P < 0.01). The results suggest that the ERβ-mediated JNK signaling pathway participates in regulating the effects of high-dose boron on the expression of genes related to the proliferation and apoptosis of rat splenic lymphocytes.